2021
DOI: 10.1002/fes3.294
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to low phosphorus was enhanced by an alternate wetting and drying regime in rice

Abstract: is an essential macronutrient for plant growth and development (Baker et al., 2015;Plaxton & Tran, 2011). Compared to nitrogen (N), P is a non-renewable resource. Despite large amounts of organic and inorganic P in natural soils, only 0.1% of the total P is available to plants because of the low solubility and rapid conversion of P compounds to unavailable or less available P after fertilizer application in the soil (Bhadouria et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Rice is also the largest consumer of water among all crops [7,8]. The water productivity of rice is lower than those of other crops [9].…”
Section: Introductionmentioning
confidence: 99%
“…Rice is also the largest consumer of water among all crops [7,8]. The water productivity of rice is lower than those of other crops [9].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the direct product of photosynthesis in the crops after anthesis, the NSC reserves stored in stems and sheaths pre‐anthesis are the important sources for grain yield (Austin et al, 1977; Duan et al, 2018). Many studies have shown that the transportation of carbon assimilates stored in the temporary source tissues to the grains can be intensified in cereal crops when facing adversary conditions like soil drying (Deng et al, 2021; Wu et al, 2019; Xu et al, 2016). In a maize experiment with different irrigation amounts, the most photosynthate was transported from leaves and stalks to kernels in the minimum irrigation regime, and the lowest transfer occurred in the maximum irrigation regime (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The dried samples of rice plant organs were used to determine both P and nonstructural carbohydrates (NSC) content. The measurement of P accumulation was using the method described by Deng et al [21]. The NSC content in the stem (including culms and sheaths) at the heading time and maturity was determined using the method of anthrone proposed by Yoshida et al [35].…”
Section: Phosphorus Content and Non-structural Carbohydrate Remobiliz...mentioning
confidence: 99%
“…However, excessive P input is a prominent problem, leading to a low PUE and environmental pollution. In response to this challenge, agronomists consider the adoption of P-efficient indica rice varieties as an important strategy to reduce P input, improve grain yield, and promote environmental sustainability [21,22]. Given that root and shoot traits directly or indirectly drive the release of soil available P content, it is therefore that substantial attention should be directed toward unraveling the relationship between PUE and plant traits in indica rice, particularly under the limited P conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation